Pengelolaan Pembelajaran IPA Terpadu di SMP Negeri 2 Kartasura Tahun Pelajaran 2015-2016 - Munandar, Arif (2016)
Knowledge of Nature (IPA) is a combination of biology, physics, and chemistry which in practice does not separate into a unified whole. Learning were substantive in education. Through two-way communication process, educators should be able to answer the needs of the mindset, skills, and character of the students or the market. The purpose of this research is to describe the management of Integrated science teaching in Public Junior High School 2 Kartasura through the planning, implementation and assessment of learning undertaken Integrated Science educators in the implementation of Integrated Science teaching and learning process. This research is classified as qualitative research with phenomenological approach, which focuses on the descriptive data in the form of sentences given by informants or observed behavior. Data were gathered through structured interviews, observation, and documentation, and data analysis techniques used in this study is a model Milles and Huberman. The results of this study indicate that the learning management Integrated Sciences in public Junior High School 2 Kartasura not run optimally. Barriers to learning science management in Public Junior high school 2 Kartasura, namely: Planning Integrated Learning science is not in accordance with the lesson plan provided by the relevant agencies. Implementation science teaching Integrated not be integrated and implemented on chemical subjects not taught, learning implementation Integrated Science is not in accordance with the Standards Process regulation minister of national education of the republic Indonesia number 41 in 2007, and the assessment of learning science oriented, the evaluation is done by two methods, namely: evaluation short-term and long-term and do Remediation.